METODE PENYULUH AGAMA DALAM MEMOTIVASI MASYARAKAT MUSLIM UNTUK MENJAUHI MAKANAN HARAM DI KECAMATAN TIGANDREKET KABUPATEN KARO - Hagiansyah Harahap; Mutiawati Mutiawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Indonesia is a country where the majority of the population adheres to Islam as their belief. The availability of halal food and products is a necessity for Muslims to fulfill their daily food needs. The role of an educator of halal products is needed to promote the practice of consuming halal food to increase awareness, understanding and knowledge about the importance of consuming halal food consistently. This study aims to determine the influence of religious instructors in motivating Muslim communities in Tigandreket District, Karo Regency to stay away from unclean foods in consuming food. As a result, it is known that several things are understood by the people in Tigandreket District, Karo Regency regarding halal food, including: the container has a halal symbol, the killing of animals is accompanied by the prayer of Allah (SWT), the method has been followed, and the processing and packaging have been completed, sanitation and kitchen conditions and cold storage areas are both adequate, food does not use alcoholic beverages or pork, is legally obtained without theft, and is produced using legal ingredients. During counseling, community openness and the involvement of other officers in socializing and providing guidance to the community help with the counseling. While the factors that hinder the process of counseling halal products are the lack of supporting media when conducting counseling such as guidebooks or assignment letters.